Penerapan Media Pembelajaran Visual Berbantuan Gambar Representatif untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Sirotul Maulana; Nur Alimah (Jurnal Didaktika Pendidikan Dasar, 2023)
The begining of this research is the observation result of social science education teacher regarding the low skill students’ critical thinking in social science education learning activity class. The goal of this research is knowing the activity of social science education learning using learning tool with representative picture done by the teacher for improving critical thinking skills of VII 6 students of SMP Negeri 5 Padang. The method used in this study is Classroom Action Research (CAR), referring to Kurt Lewin’s approach that having four steps those are planning, action, observation, and reflection. The research as conducted collaboratively by the reseacher and teachers of social science education subject in three cycles. The research result showed that there is an improvement in every indicators of one, two and three cycle. It showed that using learning tool with representative picture can have positive relation with students’ critical thingking in social science education subject in VII 6 class of SMP Negeri 5 Padang.